PRNP P39L Variant is a Rare Cause of Frontotemporal Dementia in Italian Population. - Oldoni, Emanuela; Fumagalli, Giorgio G; Serpente, Maria; Fenoglio, Chiara; Scarioni, Marta; Arighi, Andrea; Bruno, Giuseppe; Talarico, Giuseppina; Confaloni, Annamaria; Piscopo, Paola; Nacmias, Benedetta; Sorbi, Sandro; et al. (J Alzheimers Dis, 2016)
The missense P39L variant in the prion protein gene (PRNP) has recently been associated with frontotemporal dementia (FTD). Here, we analyzed the presence of the P39L variant in 761 patients with FTD and 719 controls and found a single carrier among patients. The patient was a 67-year-old male, with a positive family history for dementia, who developed apathy, short term memory deficit, and postural instability at 66. Clinical and instrumental workup excluded prion disease. At MRI, bilateral frontal lobe atrophy was present. A diagnosis of FTD was made, with a mainly apathetic phenotype. The PRNP P39L mutation may be an extremely rare cause of FTD (0.13%).
Keywords: Aged; Atrophy; Frontal Lobe; Frontotemporal Dementia; Genetic Predisposition to Disease; Humans; Italy; Language; Magnetic Resonance Imaging; Male; Memory Disorders; Memory, Short-Term; Neuropsychological Tests; Prion Proteins; Prions; Temporal Lobe

Reversible Mild Cognitive Impairment: The Role of Comorbidities at Baseline Evaluation. - Grande, Giulia; Cucumo, Valentina; Cova, Ilaria; Ghiretti, Roberta; Maggiore, Laura; Lacorte, Eleonora; Galimberti, Daniela; Scarpini, Elio; Clerici, Francesca; Pomati, Simone; Vanacore, Nicola; Mariani, Claudio (J Alzheimers Dis, 2016)
The prognostic value of mild cognitive impairment (MCI) is being questioned, with some MCI subjects reverting to normal cognition (NC). The reversion rate varies mostly depending on the study design, the setting, and both MCI and NC definitions. Previous studies have focused on the profile of subjects who revert to NC, but the role of comorbidities has not been entirely investigated. We aimed to evaluate the proportion of MCI subjects who revert to NC in a memory clinic context, focusing on the role of comorbidities. Between 2004 and 2013, 374 MCI subjects were recruited. During a mean time of 32 ± 25.5 months, 21 subjects (5.6%) reverted to NC. Subjects who reverted to NC were younger (p = 0.0001), more educated (p = 0.0001), had a better global cognition (p = 0.0001), as assessed by the Mini-Mental State Examination (MMSE) and suffered from more comorbidities (p = 0.002), as assessed by Cumulative Illness Rating Scale (CIRS) than those who developed dementia. The Cox Regression Model, constructed to adjust for the confounders, showed that the higher were the MMSE (HR = 1.83, CI 95%: 1.07-3.11) and the CIRS score (HR = 1.3, CI 95% 0.88-1.92) at baseline, the higher was the probability of returning to NC than developing dementia, though the last association was not significant. Subjects who reverted to NC were more frequently affected by respiratory (p = 0.002), urologic (p = 0.012), and psychiatric (p = 0.012) diseases. The cognitive performance of subjects with medical comorbidities could benefit from preventive strategies aimed at treating the underlying diseases.
Keywords: Analysis of Variance; Cognitive Dysfunction; Cohort Studies; Comorbidity; Female; Humans; Male; Memory; Mental Status Schedule; Neuropsychological Tests; Reference Values; Verbal Learning